Relationship Between Hg Speciation and Hg Methylation/Demethylation Processes in the Sulfate-Reducing Bacterium Pseudodesulfovibrio hydrargyri: Evidences From HERFD-XANES and Nano-XRF - Isaure, Marie-Pierre; Albertelli, Marine; Kieffer, Isabelle; Tucoulou, Rémi; Petrel, Melina; Gontier, Etienne; Tessier, Emmanuel; Monperrus, Mathilde; Goñi-Urriza, Marisol (Frontiers in Microbiology, 2020)
Microorganisms are key players in the transformation of mercury into neurotoxic methylmercury (MeHg). Nevertheless, this mechanism and the opposite MeHg demethylation remain poorly understood. Here, we explored the impact of inorganic mercury (IHg) and MeHg concentrations from 0.05 to 50 µM on the production and degradation of MeHg in two sulfate-reducing bacteria, Pseudodesulfovibrio hydrargyri BerOc1 able to methylate and demethylate mercury and Desulfovibrio desulfuricans G200 only able to demethylate MeHg. MeHg produced by BerOc1 increased with increasing IHg concentration with a maximum attained for 5 µM, and suggested a saturation of the process. MeHg was mainly found in the supernatant suggesting its export from the cell. Hg L3-edge High- Energy-Resolution-Fluorescence-Detected-X-ray-Absorption-Near-Edge-Structure spectroscopy (HERFD-XANES) identified MeHg produced by BerOc1 as MeHg-cysteine2 form. A dominant tetracoordinated βHgS form was detected for BerOc1 exposed to the lowest IHg concentrations where methylation was detected. In contrast, at the highest exposure (50 µM) where Hg methylation was abolished, Hg species drastically changed suggesting a role of Hg speciation in the production of MeHg. The tetracoordinated βHgS was likely present as nano-particles as suggested by transmission electron microscopy combined to X-ray energy dispersive spectroscopy (TEM-X-EDS) and nano-X ray fluorescence (nano-XRF). When exposed to MeHg, the production of IHg, on the contrary, increased with the increase of MeHg exposure until 50 µM for both BerOc1 and G200 strains, suggesting that demethylation did not require intact biological activity. The IHg formed species were identified as various tetracoordinated Hg-S forms. These results highlight the important role of thiol ligands and Hg coordination in Hg methylation and demethylation processes.